Economic recession (2006-2012) and changes in the health status of the Spanish population - Shirley Pérez-Romero; Juan J Gascón-Cánovas; Ernesto de la Cruz-Sánchez; José F Sánchez-Ruiz; Pedro Parra-Hidalgo; Olga Monteagudo-Piqueras (Instituto Nacional de Salud Pública, 2016)
Objective. To analyze the relationship of mental health problems in Spanish population with the economic recession (2006-2012), and find out how it affects the self-perception of health status. Materials and methods. Cross-sectional study using the National Health Survey of Spain, 2006/2007 and 2011/2012. Using logistic regression models, three in- dicators linked to mental health and perceived health were analyzed. Results. In 2011/2012 the consumption of antianxiety medications and sleeping pills increased in men and women. Mental dysfunction increased during the economic crisis in the male population. The perception of optimal health did not suffer significantly in either men or women. Conclusions. The economic recession showed a changing relation to the mental and general health of the population, coinciding with an increase in mental health disorders, such as anxiety.